2022
DOI: 10.1109/jlt.2022.3200827
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Channel Nonlinearity Mitigation in Optical Fiber Transmission Systems Using Perturbation-Based Neural Network

Abstract: In this work, a perturbation-based neural network (P-NN) scheme with an embedded bidirectional long short-term memory (biLSTM) layer is investigated to compensate for the Kerr fiber nonlinearity in optical fiber communication systems. Numerical simulations have been carried out in a 32-Gbaud dualpolarization 16-ary quadrature amplitude modulation (DP-16QAM) transmission system. It is shown that this P-NN equalizer can achieve signal-to-noise ratio improvements of ~1.37 dB and ~0.80 dB, compared to the use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In PDM optical fiber communication systems, the continuous signals can be denoted as T , where z and t represent the transmission distance and time, respectively. In optical fiber transmission link, the ⃗ Q(z, t) follows the Manakov equation as [17]:…”
Section: Feature Map Constructionmentioning
confidence: 99%
“…In PDM optical fiber communication systems, the continuous signals can be denoted as T , where z and t represent the transmission distance and time, respectively. In optical fiber transmission link, the ⃗ Q(z, t) follows the Manakov equation as [17]:…”
Section: Feature Map Constructionmentioning
confidence: 99%
“…After the transmission over the communication link dominated by ASE noise, the received symbol sequence 𝒀 = [𝑦 1 , … , 𝑦 𝑛 𝑠 ] is processed by a CM decoder, which provides the soft information of the transmitted information sequence. [13][14][15] The difference between the two symbols is defined as the vector 𝑑 𝑖,𝑗 = 𝑥 𝑖 − 𝑥 𝑗 . In this work, we consider the most common case in optical fiber communication systems, which is 𝑀 = 2, corresponding to coherent communication using two polarizations of the optical signal.…”
Section: System Model and Ase Noise 21 System Modelmentioning
confidence: 99%
“…Using neural networks to process the sequence of signal features is equivalent to gradually fusing and extracting the relationships between the features, in which the depth of the latter is well condensed. However, the breadth of the features (e.g., the power of the current signal) may be weakened during gradual feature fusion and extraction, which then impacts the nonlinear equalization results [18][19][20]. It has been shown that inter-channel crosstalk in wavelength division multiplexing WDM systems significantly affects transmission capacity and transmission distance.…”
Section: Introductionmentioning
confidence: 99%